Analisis Manfaat Menggunakan Strategi Pembelajaran Inovatif untuk Meningkatkan Hasil Belajar Siswa - Lisdayanti Tinambunan; Selvia Selvia; Delon Josephine Efrata; Vanesa Seftilavika; Elma Purwantie; Kalip Kalip (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2025)
Learning strategies are both a systematic approach and an art for managing the learning process so that learning objectives can be achieved effectively and efficiently. As a method, learning strategies are designed based on specific principles and rules derived from learning theory and educational research. This makes learning strategies a distinct field of knowledge that can be studied, developed, and applied scientifically. As an art, learning strategies demonstrate an educator's ability to creatively and flexibly utilize various learning resources, methods, and media according to student characteristics and the learning environment. A teacher who possesses sensitivity and intuition in managing learning can create a pleasant atmosphere and motivate students to be active and independent in their learning. Without a clear and directed strategy, the learning process tends to be haphazard, unfocused, and difficult to achieve. Therefore, planning and implementing appropriate learning strategies are crucial factors in the success of the educational process, as they determine the extent to which teaching and learning activities can proceed optimally and produce meaningful learning outcomes for students.